Student Management in Improving Student Discipline at Madrasah Aliyah (International Journal of Economics Management and Social Science, 2026)
This study aims to describe and analyze student management in improving student discipline at Madrasah Aliyah. This study uses a qualitative approach with a descriptive research type. The research subjects included the madrasah principal, the vice principal for student affairs, teachers, and students. Data collection techniques were carried out through observation, in-depth interviews, and documentation studies. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions, while the validity of the data was tested using source and technical triangulation techniques. The results of the study indicate that student management at Madrasah Aliyah is implemented through several stages, namely student program planning, organization, implementation, and evaluation. Student discipline planning is carried out by compiling madrasah regulations that refer to Islamic values. The implementation of student management involves all members of the madrasah through guidance, supervision, and the provision of educational sanctions and rewards. Evaluations are carried out periodically to assess the effectiveness of the discipline program. Supporting factors in improving student discipline include the commitment of madrasah leaders, the role of teachers, and parental support, while inhibiting factors include student background and environmental influences. Based on the research results, it can be concluded that well-planned and coordinated student management plays a significant role in improving student discipline at Madrasah Aliyah.